Dry Forest Reforestation for Preventing River Overflows in Peru, the Case of The Íllimo District, Lambayeque Region (2018-2019) - Nuñez Gamboa, Luis Johan (2022)
This research aims at providing an analysis of the possibilities of reforestation to prevent river overflow. It studies La Leche River, in the stretch or low course located in the Íllimo district, Lambayeque region (Peru). In addition, it provides preliminary information on the conservation status of forest species in the seasonally dry forest, and the threat of flooding due to river overflows, which occurs each year due to heavy rain. In this context, information was collected and processed to identify forest species in the study area and to then select those that -due to their anatomical structure- have more water absorption capacity, in order to mitigate adverse effects that come up when the river overflows.